Mundo comum e povoamento da paisagem : ler com O aprendiz de feiticeiro de Carlos de Oliveira - Gandolfi, Leonardo (2007)
In this study we go through the book O aprendiz de feiticeiro by Carlos de Oliveira searching for images in which the first person in the text subject, narrator, character recognises him/herself explicitly as a reader, constantly valuing the act of reading. It is thus an analysis that always bears in mind the notion of reading. We therefore circumscribe the space and the functions assumed by the reader in this work and intend to reveal his/ her manifold dimensions, which are evidenced in the poem Estalactite , from Micropaisagem. Employing, among others, a concept of mímesis that values reception, we pay particular attention to the way reference to reality is constructed through the same notion of the act of reading learnt from O aprendiz de feiticeiro.